Trade and location with land as a productive factor - Michael Pflüger; Takatoshi Tabuchi (Institute for the Study of Labor (IZA), 2008)
This paper is motivated by the fact that, contrary to its importance in practice, the role of land for production has received no attention in the new trade theory and the new economic geography. We set up a simple monopolistic competition model and we show that, due to the factor proportions effect which emerges when land is used as a productive factor besides labor, a number of tenets of the new trade and geography literature no longer hold. We also show that in order to explain the stylized facts, notably that wages are higher in larger locations, land-use for production and housing has to be taken into account. Our analysis furthermore implies that market-size based agglomeration forces are too weak to overcome the very strong congestion force associated with competition for land, unless the consumers' desire of variety (as expressed by a low elasticity of substitution) is very strong. This suggests that further agglomeration forces have to be invoked to explain the agglomeration of economic activity observed in the real world.
urn:nbn:de:101:1-20081014150
Keywords: F12; 330; Trade and location; land for production; agglomeration; relative wage; home market effect; Boden; Bodenökonomik; Monopolistischer Wettbewerb; Neue Außenhandelstheorie; Neue ökonomische Geographie; Agglomerationseffekt; Regionale Lohnstruktur; Theorie